IMPROVEMENT EFFORTS TO LEARN LESSONS ACTIVITIES CHASSIS POWER TRANSFER STANDARD COMPETENCE AND CORRECT STEERING SYSTEM WITH LEARNING METHOD DISCOVERY INQUIRY CLASS XIB SMK MUHAMMADIYAH GAMPING ACADEMIC YEAR 2013/2014 - Harry Suharto; Pairun Roniwijaya (Universitas Sarjanawiyata Tamansiswa, 2013)
The purpose of the study to determine the increase learners' learning activities subjects chassis and power transfer competency standard steering system repair discovery learning through the implementation of class XI inquiry Lightweight Vehicle Technology SMK Muhammadiyah Gamping, Sleman academic year 2013/2014. This research including action researchÂ Research conducted at SMK Muhammadiyah Gamping XIB class academic year 2013/2014 with a sample of 26 students. Techniques of data collection using questionnaire sheet, observation sheets and documentation to determine the increase in student activity. Instrument validation study using experts judgment. Analysis using descriptive statistics using the technique .Â The results showed that the increased activity of the first cycle to the second cycle include an increase of 57.7 % Visual activities; Oral activities amounted to 61.6 %; Listening activities amounted to 23.04 %; Writing activities by 8.7 %; Mental activities of 73.1 %; Emotional activities of 42.3 % ( for the spirit of the students in learning activities ); Motor activities amounted to -7.7 % ( decrease negative activity ). Based on these results can be known to most students in SMK Muhammadiyah Gamping gave a positive opinion on the use of inquiry and discovery learning method has a view that the use of inquiry discovery learning methods can be useful for students and schools themselves. Learners who have a good perception of the use of discovery learning method of inquiry he has known and fully aware of the standards of achievement of competence theory fix the steering system. Learning discovery learning methods on achievement of competency standards inquiry repair steering systems theory pleased with the learning process, they are also able to: 1 ) increase the motivation to learn, 2) improving learning achievement; 3 ) enhancing creativity; 4 ) listen, respect, and accept the opinion of the participants other students; 5 ) reduce boredom and boredom; 6 ) convince him to others by helping others and convince him to understand each other and understand each other the extent of involvement of the students affected by the size of the perceptions of learners, good learners perceptions of the learning competency standard theory repair steering systems tend to have feelings of love, has a special interest and serious about learning to follow .